2021
DOI: 10.1063/5.0044823
|View full text |Cite
|
Sign up to set email alerts
|

Regulating droplet impact on a solid hydrophobic surface through alternating current electrowetting-on-dielectric

Abstract: The phenomenon of droplet impact is commonly found in industrial and agricultural processes. The basic characteristics and theories of a droplet impacting solid walls have been extensively studied, but the regulation of the droplet impact phenomenon has not been adequately examined. This study investigates the regulation of droplet impact on a hydrophobic surface based on alternating current electrowetting-on-dielectric (AC EWOD). When a water droplet impacts a virgin Teflon surface at 1.06 m/s, the phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Meirong Song et al (2017) showed that surfactants increase the spreading diameter of water droplets impacting on to superhydrophobic substrates 25 . More recently, Vo et al (2020) and Tan et al (2021), showed that the maximum spreading is augmented by dielectrowetting, while hindering receding and even bouncing 13 , 26 . The contact time of impacting droplets has also been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Meirong Song et al (2017) showed that surfactants increase the spreading diameter of water droplets impacting on to superhydrophobic substrates 25 . More recently, Vo et al (2020) and Tan et al (2021), showed that the maximum spreading is augmented by dielectrowetting, while hindering receding and even bouncing 13 , 26 . The contact time of impacting droplets has also been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al . [23] revealed the control over drop impact on hydrophobic surfaces based on alternating current electrowetting-on-dielectric (AC EWOD). They studied the impact control mechanism of AC signal on droplets by analysing changes in spread diameter and height under varying frequencies and amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Yun et al [22] investigated and described the mechanism of droplet rebound suppression by inducing non-axisymmetric drop deformation and kinetic energy transfer between orthogonal coordinate axes. Tan et al [23] revealed the control over drop impact on hydrophobic surfaces based on alternating current electrowetting-on-dielectric (AC EWOD). They studied the impact control mechanism of AC signal on droplets by analysing changes in spread diameter and height under varying frequencies and amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Although several considerable research studies have been conducted to explore impacting droplet characteristics on hydrophobic surfaces, the main focus was to correlate the influence of Weber number, texture characteristics with the spreading and restitution coefficients. 14,15,16 The contribution of the oscillating hydrophobic surfaces to the droplet impacting characteristics has received less attention. The interaction between the droplet fluid and the oscillating hydrophobic surface involves the complicated dynamic process during droplet spreading/retraction and rebounding phases.…”
Section: Introductionmentioning
confidence: 99%